Human IL-21(+)IFN-γ(+)CD4(+) T cells in nasal polyps are regulated by IL-12 - Xiao, Li (Sci Rep, 2015)
In the previous study, we found that the levels of IL-21 in nasal polyps (NPs) were significantly increased and associated with polyp size and recurrence. However, it is unclear that the cell source of IL-21 and the regulation of IL-21 in NP tissues. In the present study, we isolated the lymphocytes from NP tissues, uncinate tissues and peripheral blood of patients with NPs. The cells were analyzed for cell surface markers, cytokines and transcriptional factors by flow cytometry. The results indicated that CD4(+) T cells were the major IL-21-exprssing cells in NP tissues and the majority of IL-21 producing CD4(+) T cells co-expressed IFN-γ or IL-17A. IL-21(+)IFN-γ(+)CD4(+) T cells in NP tissues exhibited the features of both Tfh and Th1 cells which co-expressed significantly higher amount of CXCR5, ICOS, PD-1, Bcl-6 and T-bet than did IL-21(+)IFN-γ(−)CD4(+) T cells (p < 0.05). Treatment of the lymphocytes from NP tissues with IL-12 enhanced the production of IL-21 and IFN-γ, especially the frequency of IL-21(+)IFN(−)γ(+)CD4(+) T cells (p < 0.05). The blockade of IL-12 inhibited the production of IL-21 and IFN-γ (p < 0.05). These findings indicated that IL-12 positively enhanced the generation of IL-21(+)IFN-γ(+)CD4(+) T cells having the features of both Tfh and Th1 cells in NP tissues.